Reward, learning and games. (August 2016) - Howard-Jones, Paul A.; Jay, Tim
Highlights: Understanding of the reward–memory relationship can potentially inform education. Education may benefit from learning games with rapid uncertain reward schedules. Despite significant gaps in the science, preliminary attempts at transfer show promise. Future bridging work will need to address the influence of social and individual factors. Abstract : The link between reward and learning has chiefly been studied scientifically in the context of reinforcement learning. This type of learning, which relies upon midbrain dopaminergic response, differs greatly from the learning valued by educators, which typically involves declarative memory formation. However, with recent insights regarding the modulation of hippocampal function by midbrain dopamine, scientific understanding of the midbrain response to reward may be becoming more relevant to education. Here, we consider the potential for our current understanding of reward to inform educational learning, and consider its implications for game-like interventions in the classroom.